2008
DOI: 10.1242/jeb.023655
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic costs of foraging and the management of O2 and CO2 stores in Steller sea lions

Abstract: SUMMARYThe metabolic costs of foraging and the management of O 2 and CO 2 stores during breath-hold diving was investigated in three female Steller sea lions (Eumetopias jubatus) trained to dive between 10 and 50 m (N=1142 dives). Each trial consisted of two to eight dives separated by surface intervals that were determined by the sea lion (spontaneous trials) or by the researcher (conditioned trials). During conditioned trials, surface intervals were long enough for O 2 to return to pre-dive levels between ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 28 publications
9
69
3
Order By: Relevance
“…at the end of a foraging bout, as observed in some otariids (e.g. Fahlman et al 2008). However, in the present study, the reduction in dive duration was observed immediately following vessel exposure, suggesting that disruption of breathing sequences and associated reduction in the number of breaths taken has an immediate consequence on dive duration in blue whales.…”
Section: Discussioncontrasting
confidence: 42%
“…at the end of a foraging bout, as observed in some otariids (e.g. Fahlman et al 2008). However, in the present study, the reduction in dive duration was observed immediately following vessel exposure, suggesting that disruption of breathing sequences and associated reduction in the number of breaths taken has an immediate consequence on dive duration in blue whales.…”
Section: Discussioncontrasting
confidence: 42%
“…While it is likely that the main function of a surface period is immediate recovery of the respiratory gas stores consumed during a dive, there is evidence that surface periods also function as preparation for the subsequent dive (Lea et al 1996;Halsey et al 2003a;Wilson 2003). Second, divers are presumed to reload their oxygen stores to the same level after each dive; however, at least in some cases, divers allow their oxygen stores to run down over a number of dives rather than fully recovering their stores after each one (Fahlman et al 2008a; see also Ydenberg and Forbes 1988). Third, there may be indirect metabolic costs, such as hypothermia (Enstipp et al 2006), that accrue during diving that are met not during the surface periods between those dives but rather during an elongated surface period after a diving bout (de Leeuw 1996;Richman and Lovvorn 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gliding is a hallmark of the energy-conserving behavioral repertoire for diving marine mammals (Williams et al, 2000). This locomotor strategy, coupled with a low cost of transport (Williams, 1999) and diving bradycardia , suggests that our use of AMR may overestimate diving costs for the majority of the dive (Fahlman et al, 2008a). Thus, by underestimating prey density and overestimating diving costs, our calculations of foraging efficiency may represent conservative (i.e.…”
Section: Foraging Costs and Energetic Efficiencymentioning
confidence: 99%